2005
DOI: 10.1007/s10350-005-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

A Defunctioning Ileostomy Does Not Prevent Clinical Anastomotic Leak After a Low Anterior Resection: A Prospective, Comparative Study

Abstract: A diverting stoma does not reduce postoperative anastomotic leak rate. Rather, it reduces the otherwise catastrophic effects of an anastomotic leak such as fecal peritonitis and septicemia. An ileostomy carries certain morbidity and also adds to the cost of the entire operation. Therefore, it should not be performed routinely. Instead, it should be performed selectively in patients with poorly prepared bowels, coupled with a distal limb washout, and in patients with significant comorbidities who can ill afford… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
128
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(148 citation statements)
references
References 16 publications
11
128
0
9
Order By: Relevance
“…The two modus are not quite comparable, because the introduction of TME has resulted in very low anastomoses in patients with a tumour below 10 cm (ultra low tumor is below 4 cm) from the anal verge (wang er al., 2010). In the present register, the tumour level was recorded, our results were similar to those of others showing a higher risk of leakage for low tumours (Gastinger et al, 2005;Wong et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…The two modus are not quite comparable, because the introduction of TME has resulted in very low anastomoses in patients with a tumour below 10 cm (ultra low tumor is below 4 cm) from the anal verge (wang er al., 2010). In the present register, the tumour level was recorded, our results were similar to those of others showing a higher risk of leakage for low tumours (Gastinger et al, 2005;Wong et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…324 hasta ise anastomoz kaçağı nedeniyle reopere edilerek sekonder ileostomi iş-lemi yapılmıştır. Her iki grupta da anastomoz kaçağı açı-sından (%3,8 ve %4'sırasıyla) farklılık bulunamamıştır (11). Yine koruyucu ileostomisiz hastalara göre stomalı hastalar mortalite yönünden birkaç çalışmada incelenmiş.…”
Section: Discussionunclassified
“…As some surgeons believe that "the lesser anastomotic site fecal contamination, the lesser chance of anastomotic site leakage", using diverting ileostomy or colostomy would be a constant part of their low or ultralow anterior resection [1][2][3][4][5][6][7][8]; although several recent studies have not confirmed this idea, and only persisted on less complication of the possible leakage such as the pelvic sepsis [11,19] or and less operational needs for further possible leakages [23,28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Diverting stomas for low and ultralow rectal anastomosis are being constructed routinely in some colorectal centers [1][2][3][4][5][6][7][8] based on crediting the fact that creating route diverting stomas, and thereby making a space from the anastomosis, lowers the anastomotic leakage incidence; whereas, some other centers have shown the reverse [9][10][11][12][13]. Furthermore, the stoma itself would increase the morbidity in construction time, life period, and closure time, which also in its place needs reoperation and hospitalization, and so has its own morbidity and mortality [14][15][16].…”
Section: Introductionmentioning
confidence: 99%